Design and Development of an Isothermal-Based Contrast Media Storage Device for Optimal Temperature Stability - Sagita Yudha; Nerifa Dewilza; Noviardi Prima Putra; Agusril Agusril (Journal of Public Health Indonesian, 2026)
Contrast media are used in radiological diagnostic imaging to enhance the visibility of internal body structures. The storage of contrast media must adhere to temperature standards, specifically around 37°C, to maintain its quality. The use of inadequate storage equipment can lead to crystallization or a decrease in the function of the contrast media. This research aims to design and build an automatic contrast media storage device, test its functionality, and evaluate its performance based on applicable storage standards. This research uses an exploratory approach. The designed tool is in the shape of a square box, made of plywood with an aluminum coating on the outside and lead on the inside. The main elements include an electric heater, a digital thermostat for temperature control, and LED lights for illumination. Function tests are conducted using a checklist assessment, while performance tests are evaluated based on ease of use, safety, and effectiveness. The results of the functional test demonstrate that every part of the apparatus, including the temperature controller and heating element, functions effectively to keep the contrast media temperature at 37°C. The equipment is safe, efficient, and easy to use, according to the performance test findings. A > 80% feasibility level was attained in both experiments. The automatic contrast media storage device's design and construction were successful in preserving the contrast media's quality, boosting radiographers' productivity, and making it appropriate for use in medical facilities. However, in rooms with air conditioning, the device's effectiveness is subpar. To enhance the device's performance in different environmental circumstances, more development is required.